New Evacuation Management Criteria for Potential Landslides Based on Experimental Studies - Choi, Sun-Gyu; Jung, Min-Su; Suk, Jae-Wook; Kim, Ho-Jong; Kang, Hyo-Sub; Jeong, Hyang-Seon; Song, Hyo-Sung (Frontiers in Environmental Science, 2022)
This study developed and verified landslide resident evacuation management criteria through the analysis of surface behaviors (the surface displacement and slope) to minimize casualties and property damage caused by landslides. First, for the surface-displacement-based resident evacuation management criteria, short-term-based management criteria were developed through the analysis of experimental results, and long-term-based resident evacuation management criteria were developed through the analysis of site collapse data. Furthermore, the reliability of the developed criteria was verified through additional experiments and comparison with the results of previous domestic and overseas studies. Next, surface-slope-based resident evacuation management criteria were developed through the analysis of experimental results, and the reliability of the developed criteria was verified through additional experiments. Finally, the phased management criteria of these two criteria categories were directly compared and their similar results (i.e., warning times) were verified. This analysis confirmed that the investigated surface-slope-based management criteria can serve as an auxiliary form of the surface-displacement-based resident evacuation management criteria.